Status quo of urban logistics in science, politics and practice. Developing an approach for urban logistics projects in the Hanover region. - Viebahn, Christoph; Auf der Landwehr, Marvin; Trott, Maik; Gusig, Lars-Oliver (My University, 2020)
As foundation for initiating an urban logistics project in Hanover, a detailed analysis on existing tools and measures has been conducted. By merging the results of three different multi-national state of the art analysis, a group of six categories with in total 23 measures could be classified, evaluating their environmental and economic impact. A list of 63 international examples gives a solid overview to support new project teams with the means to identify and prioritize a set of actions to be taken into closer consideration. The paper pools the main issues of meta-studies screening science (Wolpert and Reuter, 2012), delivering a synopsis of the political approach (EC 2012) and fitting best practice (van Audenhove et al.2015, Civitas 2015, BestUFS 2015). Selected measures are explicitly examined in order to provide additional insights on the status of different logistics concepts and complement priory defined categories, measures and examples. By conclusively elaborating the status of existing measures, new projects are supported in terms of project priorization, set-up, initiation, execution and assessment.
Keywords: Stadtlogistik; Forschungsprojekt; Entwicklungsprojekt; Literaturauswertung; Screening; Best Practice; Internationaler Vergleich